2011
DOI: 10.1021/cg200267x
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Interactions in an Unusual 2D Coordination Polymer Including Di-2-pyridylketone-Methoxilated Anion, (1,1)-Azide, and Rare (1,1,3,3)-Azide Bridging Ligands

Abstract: ACKNOWLEDGMENTThis work was supported by the Universidad del País Vasco (UPV/EHU) (UPV00169. EHU 2010/14), the Spanish Ministerio de Ciencia y Tecnología (MCYT) (CTQ2005-05778-PPQ), and the Basque Government (project IT-282-07). N.D. P. thanks UPV/EHU for financial support from "Convocatoria para la concesi on de ayudas de especializaci on para investigadores doctores en la UPV/EHU (2008)".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…These two-dimensional layers are packed together to form three-dimensional framework structures. In addition, similar two-dimensional structures have been reported, for example, [Cu4(dpk 3CH 3 O) 2 (N 3 ) 6 ]n and [Co(L) 2 (SCN) 2 •2(CH 3 CN)•2(dmf)]n [10,11].…”
Section: Discussionsupporting
confidence: 70%
“…These two-dimensional layers are packed together to form three-dimensional framework structures. In addition, similar two-dimensional structures have been reported, for example, [Cu4(dpk 3CH 3 O) 2 (N 3 ) 6 ]n and [Co(L) 2 (SCN) 2 •2(CH 3 CN)•2(dmf)]n [10,11].…”
Section: Discussionsupporting
confidence: 70%
“…Utilizing the aforesaid advantages of Cd(II)/Zn(II) metal and salen based tetradentate acyclic bi‐compartmental ligands many research groups have reported bi, tri, hetero or polynuclear complexes in presence of organic or inorganic linkers as auxiliary moieties . In order to construct diverse topologies and frameworks of salen based ligands, inorganic bridging azide co‐ligands is very attractive owing to their bridging propensity of adjacent metal ions due to their smaller length, rigidity and versatile coordination modes of donor atoms such as μ 1,1 ‐(end‐on, EO), μ 1,3 ‐(end‐to‐on, EE), μ 1,1 , 1 ‐, μ 1,1 , 3 ‐, μ 1,3 , 1,1 ‐, μ 1,1 , 3,3 ‐ etc . Hence Cd(II)/Zn(II) bi or tri‐nuclear complexes which are derived from salen‐ type Schiff base ligands and azide ions as co‐ligands are of current interest to both structural and synthetic chemists because of their unique pale color, higher thermally stability and possible strong attracting photoluminescence properties .…”
Section: Introductionmentioning
confidence: 99%
“…Self‐assembled supramolecular architectures are of great interest due to the aesthetic beauty and potential as functional materials. In supramolecules, the individual building blocks may be self‐assembled by covalent bonds, coordinate bonds and weak interactions like hydrogen bonds, π⋅⋅⋅π stacking interactions, halogen bonds, carbonyl⋅⋅⋅carbonyl interaction, etc . Coordination polymers, including metal organic frameworks, belong to a class of supramolecules in which the nodes are metal complexes and the linkers are bridging organic or inorganic ligands .…”
Section: Introductionmentioning
confidence: 99%
“…In supramolecules, the individual building blocks may be self‐assembled by covalent bonds, coordinate bonds and weak interactions like hydrogen bonds, π⋅⋅⋅π stacking interactions, halogen bonds, carbonyl⋅⋅⋅carbonyl interaction, etc . Coordination polymers, including metal organic frameworks, belong to a class of supramolecules in which the nodes are metal complexes and the linkers are bridging organic or inorganic ligands . Regarding inorganic bridging ligands, azide is a nice linker because it can coordinate to metal ions in various modes such as μ 1,1 ‐ (end‐on; commonly expressed as EO), μ 1,3 ‐ (end‐to‐end; commonly expressed as EE), μ 1,1,1 ‐, μ 1,1,3 ‐, μ 1,1,1,1 ‐, and μ 1,1,3,3 ‐ ,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation